Soil chemical attributes and nutritional status of soybean and maize intercropped with Urochloa under nitrogen rates - Ribeiro Barzan, Renan; Jordão, Luiz Tadeu; Firmano, Ruan Francisco; Secato, Thiago Rodriguero; Lima, Fabio; Ribeiro Barzan, Liége; de Oliveira, Adilson; Castro, Cesar; Alexandre Costa Crusciol, Carlos [UNESP]; Zucareli, Claudemir (Wiley, 2021)
Maize (Zea mays L.) intercropping with forage plants has been adopted with the main goal of promoting benefits on soil physical properties. However, a better understanding of soil chemical attributes and crops nutrition under this system is necessary. The objective was to verify whether intercropping maize with Urochloa ruziziensis (Germ. & Evrard) Crins, a tropical forage grass originating in Africa, associated with N rates, could provide modifications on soil chemical attributes and nutritional status of maize and soybean [Glycine max (L.) Merr.] grown in succession. The experiment was carried out for three agricultural years at field conditions in a Rhodic Hapludox soil under no-till system in the state of Paraná, Brazil. Fall/winter (March–August) maize cropping systems, sole or intercropped with U. ruziziensis, were associated with four nitrogen (N) rates (0, 40, 80, and 120 kg ha–1 N) applied as ammonium nitrate (30% N). The soil chemical attributes were not influenced by the factors studied. The N rates linearly increased phosphorus (P), sulfur (S), and copper (Cu) concentrations in maize leaves by 29, 30, and 49%, respectively, whereas for soybeans, only the concentration of manganese was raised by 15%. Maize leaf calcium was linearly reduced with N rates only when sole cropped, up to 15%. The cropping systems did not influence nutrient concentrations in soybean leaves; however, maize leaf concentrations of P within 80 and 120 kg ha–1 of N, as well as potassium, S, and Cu at all N rates, were reduced in 9, 6.5, 6.5, and 8%, respectively.